The Influence of Talent Management Strategy on Product Innovation and Marketing Performance - Elly Karmeli; Noni Antika Khairunnisah; Effendy Gunardi; Siti Mujanah (Business Management, 2025)
This study aims to analyze the influence of talent management strategy on product innovation and company marketing performance. Talent management strategy is seen as a strategic approach in human resource management that is oriented towards creating competitive advantage through the development, placement, and retention of talented individuals. Product innovation acts as a mediator that bridges the contribution of talent management to achieving optimal marketing performance. The research method used is quantitative with an explanatory approach. Data were collected through questionnaires distributed to 150 respondents consisting of HR, innovation, and marketing managers in medium and large manufacturing companies. Data analysis was carried out using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results showed that talent management strategy has a positive and significant effect on product innovation and marketing performance. In addition, product innovation also has a significant effect on marketing performance and partially mediates the relationship between talent management strategy and marketing performance. This finding confirms that the effectiveness of talent management strategy has strategic implications for the company's ability to create innovative products and increase competitiveness in the market.